2005
DOI: 10.1161/01.hyp.0000182658.04299.15
|View full text |Cite
|
Sign up to set email alerts
|

Association of the T8590C Polymorphism of CYP4A11 With Hypertension in the MONICA Augsburg Echocardiographic Substudy

Abstract: Abstract-Genetic variants of the arachidonic acid monooxygenase CYP4A11 result in decreased synthesis of 20-hydroxyeicostatetraenoic acid and experimental hypertension. Moreover, in humans, the T8590C polymorphism of CYP4A11 displayed association with arterial hypertension. The aim of the present study was to further investigate this association in a large population-based sample. Therefore, the participants of the echocardiographic substudy of the third MONICA (MONitoring trends and determinants In CArdiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
68
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 22 publications
6
68
2
Order By: Relevance
“…Both the CYP4A11 F434S and CYP4F2 V433M genotype frequencies observed in the present study were in agreement with previous studies examining these mutations. 3,11,20 Gainer et al 11 had demonstrated previously an in vitro loss of function as a result of the CYP4A11 TC/CC genotype. The lack of an effect of the TC/CC genotype on BP in this cohort is intriguing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both the CYP4A11 F434S and CYP4F2 V433M genotype frequencies observed in the present study were in agreement with previous studies examining these mutations. 3,11,20 Gainer et al 11 had demonstrated previously an in vitro loss of function as a result of the CYP4A11 TC/CC genotype. The lack of an effect of the TC/CC genotype on BP in this cohort is intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…11 Although Mayer et al 20 observed a tendency toward elevated BP in the CC genotype compared with TT/TC genotypes (recessive effect model), when the CC/TC genotypes were combined (dominant effect model), the association with high BP was lost. 20,21 Both of these studies suggest that the CYP4A11 isoform is found at a location in the kidney where 20-HETE functions as a natriuretic, such that loss of production causes elevations in BP. The lack of a relationship between BP and individuals with the TC or CC genotype in our study could be because of the relatively small number of individuals with these genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selective disruption of the murine Cyp4a10 (6) and Cyp4a14 (7) genes leads to hypertensive phenotypes that are thought to reflect changes in renal 20-HETE production arising through distinct mechanisms. Interestingly, an allelic variant encodes a human CYP4A11 with reduced catalytic activity that is associated with an increased risk for hypertension in studies of three independent cohorts (8,9). P450s 4F2 and 4F3B are highly similar in amino acid sequence and display overlapping catalytic activity profiles.…”
mentioning
confidence: 99%